IoT-based Smart-homes to Increase Home Selling Price - Harian Putra, Trio; Erfan Rohadi; Indrazno Sirrajudin (International Journal of Frontier Technology and Engineering, 2023)
Smarthome is a system that has been programmed and can work with the help of a microcontroller to integrate and control a device or home appliance automatically and efficiently. The purpose of creating this technology is to facilitate energy savings, get comfort and be able to control it only with a smartphone. In the research entitled "IoT based Smart Home Automation System using Sensor Node". This stage of development will use several microcontrollers as sensor nodes. Microcontroller nodes will control such as lights, doors, fans. In this study, it used several types of sensors such as RFID, reed switch, temperature and microcontrollers that will be used by the ESP8266 MCU Node. All data from sensor readings will be sent to the Blynk server. As a data viewer and control center will use the Blynk application. This can also increase the selling price of the house to be sold by the developer.